A Student Evaluation of an Occupational Therapy Apprenticeship - Liddell, Jamie; Izzard, Eleanor; Elliott, Sarah; Loft, Georgia (International Journal of Practice-based Learning in Health and Social Care, 2023)
Apprenticeships are becoming an increasingly popular means of training healthcare professionals; providing an opportunity to earn and study simultaneously in order to gain nationally recognised qualifications. However, there is currently a lack of evaluative data on student experience of Occupational Therapy (OT) or Allied Health Professional (AHP) apprenticeship schemes. The aim of this study was to evaluate the perspectives of five apprentices who commenced the Kent Community Health NHS Foundation Trust (KCHFT) OT Apprenticeship in January 2020. A qualitative interpretive approach was utilised to analyse semi-structured interview data. Subsequent thematic analysis identified three key themes from the data: support (peer-support, support from employer, and applying theory to practise), organisation (University, time-management and learning needs), and communication (University, and stakeholder expectations). Findings from this study emphasise the importance of clear communication and management of expectations between stakeholders, effective induction processes, and a commitment to supporting mentors and workplace teams within the clinical arena. Future evaluations should consider the perspectives of other stakeholders within apprenticeship programmes.